Analisis Gaya Kepemimpinan Transformasional Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di Taman Kanak-Kanak Pertiwi V Karangmojo - Ardani, Deviana Rizki; Agustina, Agmya Putri; Ayu, Aisyah Setya (DIKLINKO JOURNALS PUBLISHER, 2024)
Leadership can be interpreted as a process of processing, empowerment and supervision that a leader applies to the person he leads. This research aims to determine the Transformational Leadership Style Of School Principals in Improving Teacher Performance at Pertiwi V Karangmojo Kindergarten. This research uses descriptive qualitative research methods, using direct observation, interviews and documentation. The research subjects were school principals and teachers. The results of research on Analysis of the Transformational Leadership Style of School Principals in Improving Teacher Performance at the Pertiwi V Karangmojo Kindergarten are good. Transformational leadership indicators are manifested in six components, namely; reformer, sets an example, encourages subordinate performance, acts on a value system, continuously improves abilities and is able to face complex problems. Teacher performance indicators are realized in three components, namely; the ability to prepare learning plans, the ability to carry out learning and the ability to carry out assessment of learning outcomes.